2012
DOI: 10.1016/j.bpj.2012.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Activation of Cells Induces Chromatin Remodeling Preceding MKL Nuclear Transport

Abstract: For cells to adapt to different tissues and changes in tissue mechanics, they must be able to respond to mechanical cues by changing their gene expression patterns. Biochemical signaling pathways for these responses have been elucidated, and recent evidence points to the involvement of force-induced deformation of the nucleus. However, it is still unclear how physical cues received at the plasma membrane (PM) spatiotemporally integrate to the functional chromatin organization of the cell nucleus. To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
156
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 57 publications
8
156
0
Order By: Relevance
“…Neither myosin IIA nor myosin IIB was found to be associated with the perinuclear actin rim, and inhibition of myosin II contractility did not affect formation of this actin structure. Although various studies have reported observations of actin reorganization on mechanical stimuli (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(14)(15)(16)(17), the transient perinuclear actin polymerization is revealed here for the first time to our knowledge.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Neither myosin IIA nor myosin IIB was found to be associated with the perinuclear actin rim, and inhibition of myosin II contractility did not affect formation of this actin structure. Although various studies have reported observations of actin reorganization on mechanical stimuli (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(14)(15)(16)(17), the transient perinuclear actin polymerization is revealed here for the first time to our knowledge.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, local application of force through fibronectin or collagen-coated beads trapped by optical or magnetic tweezers leads to the local reorganization of the actin cytoskeleton. This response is associated with reinforcement of bead attachment (11), recruitment of additional actin-associated proteins (12), and activation of a variety of signaling pathways (13)(14)(15)(16)(17). Most studies to date have explored the effects of force on actin structures directly associated with the sites of force application, such as focal adhesions and stress fibers.…”
mentioning
confidence: 99%
“…Chromatin dynamics can be induced by nuclear ATPases such as polymerases, topoisomerases, and chromatin remodeling complexes at millisecond timescales (58-60). However, recent findings suggest that chromatin dynamics can also result from matrix remodeling (42,43). In addition, perturbation of cytoskeletal filaments via RNA interference affects histone diffusion timescales (7).…”
Section: Linc Complex and Microtubules Affect Amplitude Of Nuclear Areamentioning
confidence: 99%
“…With the cytoskeleton physically linked to the nucleoskeleton, these extracellular mechanical signals can therefore be used to mediate changes in chromatin structure. Active cytoskeletal forces can mediate the mechanotransduction to the nucleus, to remodel 3D chromosome organization as well as permissivity to chromatin structure by regulatory molecules (42,43). Cytoskeletal to nuclear links are also essential to the maintenance of poised euchromatin and more repressive condensed chromatin, i.e., heterochromatin assembly (44).…”
mentioning
confidence: 99%
“…While biochemical signals can alter gene expression by triggering intracellular signalling cascades, intercellular and cell-ECM biomechanical interactions control tensional forces which are conducted through the cytoskeleton to the cell nucleus (Chiquet, 1999). These forces control the shape of cells and the cell nucleus and have been shown to regulate chromatin organisation and hence gene expression (Iyer et al, 2012). The extracellular microenvironment is, therefore, crucial for regulating cell behaviour-it enables cells which contain identical genetic information to behave in a tissue-specific and synchronized manner (Bissell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%